RANCANG BANGUN ALAT IMPACT TEST DENGAN METODE IZOD MENGGUNAKAN STANDAR ASTM E23 - Erwin, Erwin; Lubis, Asnawi; Ansyori, Anang (Bhinneka Multidisiplin Journal, 2025)
An increasingly advanced era, the need for buildings is increasing, especially in the field of architecture that uses metal as its main material. However, all of that must be balanced with the feasibility of the design, before implementing the design, the material must be tested first. Impact testing is a test used to measure the resistance of a material to impact loads. Impact testing attempts to simulate the operating conditions of materials commonly found in transportation and construction equipment. Loads always occur suddenly, not slowly. For example, the change in a car bumper due to an accident or a ship hitting a coral reef while sailing at sea. This study aims to create an impact test tool using the izod method to measure impact energy and metal impact strength. The methodology in this study is a literature study, design, workmanship, and tool testing. The iron nako specimen with a length of 75 mm, a width of 10 mm and a height of 10 mm is then notched at a point 28 mm from the end of the specimen with a U notch to be carried out in the izod method impact test using the ASTM E23 standard, namely the pendulum impact tester at ambient temperature and low temperature and high temperature conditions. In the test of specimens at a temperature of 0°C, the impact energy value is 151.332 J, and the test of specimens at a temperature of 20°C, the impact energy is 160.007 J. While for ambient temperature or 30°C, the impact energy is 165.763 J. In the test of specimens at a high temperature of 45°C, the impact energy is 177.163 J, and the specimen at a temperature of 60°C, the impact energy is 188.365 J. In the impact test of the ASTM E23 izod method that has been carried out, the fracture of nako iron can become ductile if the temperature of the specimen is increased. It can be concluded that the higher the temperature, the more the specimen fracture tends to experience ductile fracture.